Density functional theory study on the molecular structure of loganin. Issue 6 (2011) - Pandey, Anoop Kumar; Siddiqui, Shamoon Ahmad; Dwivedi, Apoorva; Raj, Kanwal; Misra, Neeraj
Abstract : The computational Quantum Chemistry (QC) has been used for different types of problems, for example: structural biology, surface phenomena and liquid phase. In this paper we have employed the density functional method for the study of molecular structure of loganin. The equilibrium geometry, harmonic vibrational frequencies and infrared intensities were calculated by B3LYP/6-311G (d, p) method and basis set combinations. It was found that the optimized parameters obtained by the DFT/B3LYP method are very near to the experimental ones. A detailed conformational analysis was carried out. A detailed interpretation of the infrared spectra of loganin is also reported in the present work. The FT-IR spectra of loganin were recorded in solid phase. The thermodynamic calculations related to the title compound were also performed at B3LYP/6-311G (d, p) level of theory.